Improving Students Vocabulary Through Crossword Puzzle at Seven Grade of SMP Kristen Tounwawan - Dolwoy, Novren Kenneth; Hukom, James Salmon; Kamanasa, Louisa Sarah (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2024)
This study aimed to improve vocabulary mastery through crossword puzzles among grade VII students of SMP Kristen Tounwawan in the academic year 2024/2025. This action research study was conducted at grade VII of SMP Kristen Tounwawan. It consisted of two cycles with five meetings in each one. The data were qualitative from classroom observation during the teaching and learning, interviews with the teacher and the students, and taking photographs. The data were in the form of vignettes, interview transcripts, and pictures. The validity of the research was established based on the criteria validity process, including democratic validity, outcome validity, process validity, catalytic validity, and dialogue validity. The trustworthiness of the data was employed by applying triangulation and theoretical triangulation. The result of this study concluded that there were improvements in student's vocabulary mastery. From the result of classroom observation, the students are better at using vocabulary during the teaching and learning process. The student's involvement during the implementation. Additionally, the implementations of crossword puzzles and the complementary action were successful in helping the students understand new words and learn English better. To conclude, the student's vocabulary mastery was improved by implementing crossword puzzles